EFEKTIVITAS PENYULUHAN KESEHATAN TENTANG PERAWATAN PAYUDARA TERHADAP PENGETAHUAN IBU HAMIL DI PUSKESMAS PRAMBANAN - Uswatun Qoyyimah, Anna; Wahyuni, Sri; Dynamurti Wintoro, Piscolia; Khotimah, Chusnul (INVOLUSI: Jurnal Ilmu Kebidanan, 2023)
Conditions pregnancy makes, changes in the skin, and changes in the breasts. Breast care during pregnancy is an important part that must be considered in preparation for breastfeeding the baby and improving blood circulation. Based on the results of interviews with 15 pregnant women, there were 12 pregnant women who did not know proper breast care techniques. The purpose of this study was to determine the effectiveness of health education about breast care on the knowledge of pregnant women at the Prambanan Health Center. This type of research is quasi experimental research (quasi experimental designs) with a one group pretest-posttest research design. The population in this study were 30 second and third trimester pregnant women and the sample in this study were 18 second and third trimester pregnant women using accidental sampling technique. Statistical test results using the Wilcoxon signed rank test analysis obtained a significance P = 0000 (<0.005). The conclusion of this study is that health education about breast care is effective in increasing the knowledge of pregnant women at the Prambanan Health Center. Suggestions from this study pregnant women can be more active in participating in classes for pregnant women held by village midwives or the puskesmas.